Early onset metastatic colorectal cancer in patients receiving panitumumab‐based upfront strategy: Overall and sex‐specific outcomes in the Valentino trial. Issue 10 (23rd June 2022) - Raimondi, Alessandra; Randon, Giovanni; Prisciandaro, Michele; Pagani, Filippo; Lonardi, Sara; Antoniotti, Carlotta; Bozzarelli, Silvia; Sartore‐Bianchi, Andrea; Tampellini, Marco; Fanchini, Laura; Murialdo, Roberto; Clavarezza, Matteo; et al.
Abstract: Anti‐EGFRs plus doublet chemotherapy is considered the optimal upfront option for RAS / BRAF wild‐type left‐sided metastatic colorectal cancer (mCRC). Early‐onset (EO) mCRC has an increasing incidence and its prognostic/predictive role and management is debatable. We performed a post hoc analysis of Valentino study, that randomized RAS wild‐type mCRC patients to two panitumumab‐based maintenance regimens after FOLFOX/panitumumab induction. We assessed the safety and efficacy outcomes in patients stratified for age (<50/≥50 years old). We assessed progression‐free survival (PFS), overall survival (OS), response rate (ORR), rate of treatment‐related and panitumumab‐related adverse events (AEs) and quality of life (QoL). In 229 patients enrolled, 35 (15%) had EO mCRC, with a higher rate of female sex ( P = .020) and lower rate of primary tumor resection ( P = .001). Median PFS and OS were 10.9 vs 10.8 months ( P = .593) and 28.1 vs 27.5 months ( P = .865) in patients <50 and ≥50 years old, respectively, with no significant impact of maintenance arm. ORR and disease control rate were 74% vs 65% ( P = .337) and 97% vs 81% ( P = .013) in patients <50 or ≥50 years old. In younger patients, a trend for increased chemotherapy‐related AEs (peculiarly anemia) was shown, while significantly decreased EGFR‐related hypomagnesemia and increased skin rash were reported. No significant differences in treatment intensity or QoL were observed. In patients with EO mCRC and RAS wild‐type status, we found no differences in terms of survival outcomes based on age when selecting maintenance strategies. Management of treatment‐related AEs should consider the differential toxicity profile of age and sex. What's new?: In patients with RAS and BRAF wild‐type metastatic colorectal cancer (mCRC), doublet chemotherapy with antiepidermal growth factor receptor (anti‐EGFR) agents is a recommended upfront regimen. However, data on the influence of younger age on the efficacy and safety outcomes of an EGFR‐based first‐line treatment strategy remain scant. In this post hoc analysis of the Valentino study, the authors report no significant differences in survival outcomes between patients <50 and ≥50 years old but reveal a differential toxicity profile. Rather than an intensification/modulation of the therapeutic schedule, the results support a differential toxicity management/prevention approach according to age and sex.